Genetic and environmental influences on beef cattle production in Zambia. 1. Factors affecting weaner production from Angoni, Barotse and Boran dams - Thorpe, W.R.; Cruickshank, D.K.R.; Thompson, R. (Cambridge University Press, 1980)
Factors influencing reproductive performance of Angoni, Barotse, and Boran under ranching conditions are examined. Five years reproduction records of 675 Angoni, 731 Barotse and 815 Boran were analysed. Calving percentages were 82.5, 78.1 and 75.4 for Angoni, Barotse and Boran, respectively. Year had significant influence on calving and weaning percentage in all breeds. Age of dam and status at mating was only important in the Angoni breed, in which lactating dams produced more calves than dry dams. Mean calf-weaning weights were 147.3, 167.0 and 169.5 kg for the Angoni, Barotse and Boran dam breeds respectively. Hereford, Friesian and Boran bulls sired heavier progeny than Angoni and Barotse. Dam live weights at the beginning of the breeding season were 313, 357 and 348 kg for the Angoni, Barotse and Boran breeds respectively. Angoni and Boran dams reached maximum live weight at 7 years and Barotse at 9 years.